Doing qualitative research - Silverman, David (Sage, 2017)
"Accessible, practical, and packed with indispensable advice, this bestselling textbook is the perfect hands-on guide for any student embarking on their own research. With expert advice from the author and real-life experiences from students, this book shows you how to go from the ideas of research to the practicalities of designing, conducting, and writing about your research yourself." -- Provided by publisher.